Subcutaneous Injection of Oxyfluorfen Herbicide to the Forearm: Case Report - Couceiro, José; Garcia-Portal, Gonzalo; Garcia, Olga (The Surgery Journal, 2017)
Background Oxyfluorfen, a commercially available pesticide, commonly used for weed control in crop production, has been studied in terms of its toxicity, its carcinogenic properties, and its teratogenicity. We have found no reports, however, of the effects produced by an oxyfluorfen injection to the upper limb.Methods We present the case of a 40 years old psychiatric patient, who reportedly injected her forearm accidentally while fumigating her garden. She was treated with irrigation and open forearm fasciectomy.Results At 6 months, the patient had some tenderness at the scar; she wanted no further procedures done.Conclusion Oxyfluorfen appeared to produce a chemical burn to the forearm tissues including the fascia, removal of the chemical product, and a limited fasciectomy, resulted in a favorable outcome.
Keywords: oxyfluorfen; herbicide; injection; fasciectomy